Assessment of the hybridization between rhesus (Macaca mulatta) and long‐tailed macaques (M. fascicularis) based on morphological characters. Issue 2 (10th September 2015) - Hamada, Yuzuru; San, Aye Mi; Malaivijitnond, Suchinda
ABSTRACT: Objectives: Hybridization between rhesus ( Macaca mulatta ) and long‐tailed ( M. fascicularis ) macaques has become a focal point of interest. The majority of such studies have evaluated their genetics, but not their morphological characters. Materials and Methods: We analyzed morphological characters of eight free‐ranging populations of Indochinese rhesus and long‐tailed macaques distributed at the proposed hybrid zone (15.75–21.58° N) in comparison with one population each of Chinese and Indian‐derived rhesus macaques and three populations of Sundaic long‐tailed macaques. Results: Chinese and Indian rhesus macaques had a heavier body mass, longer crown‐rump length, shorter relative facial length and relative tail length, and a greater contrast of reddish and yellowish dorsal pelage color than the Sundaic long‐tailed macaques for which the latter three parameters could be used to visually discriminate between the two species. Although the morphological characters of Indochinese rhesus and long‐tailed macaques were intermediate between the Chinese/Indian rhesus and Sundaic long‐tailed macaques, they were more similar to their respective conspecifics. The species‐specific characters of a shorter tail (<70%) and a bipartite pelage color pattern were retained in the Indochinese rhesus macaques while the longer tail (>90%) and no bipartite pattern was found in the Indochinese long‐tailed macaques. No morphological cline was observed across the species and the variations were abrupt to some extent. Discussion: The hybridization between rhesus and long‐tailed macaques may be results of multiple contacts and isolations over a long period of time, thus their evolutionary history should not be drawn solely by genetic or morphological analysis. Am J Phys Anthropol 159:189–198, 2016. © 2015 Wiley Periodicals, Inc.